Molecular Imaging of Fibroblast Activation Protein in Response to Cardiac Injury Using [68Ga]Ga-DATA5m.SA.FAPi - Victoria Weissenböck; Lukas Weber; Michaela Schlederer; Laura Silva Sousa; Anna Stampfer; Simge Baydar; Thomas Nakuz; Raffaella Calabretta; Ana Isabel Antunes Goncalves; Xiang Li; Frank Rösch; Bruno K. Podesser; et al. (Pharmaceuticals)
Background/Objectives: Fibroblast activation protein (FAP) has gained tremendous traction as a target for tumor imaging and cancer treatment, while also playing a key role in fibrosis. Our study aimed to evaluate [68Ga]Ga-DATA5m.SA.FAPi for PET imaging of replacement fibrosis following myocardial infarction (MI) or interstitial fibrosis associated with hypertrophy. Methods: MI or transverse aortic constriction (TAC)-induced hypertrophy was induced in C57BL/6 mice, with sham-operated animals serving as controls. At multiple time points during disease progression (1, 2, and 6 weeks post-surgery), [68Ga]Ga-DATA5m.SA.FAPi PET/CT scans were performed, followed by ex vivo investigations. Additionally, in vitro cell uptake experiments simulating hypertrophy were conducted. Results: Cardiac uptake of [68Ga]Ga-DATA5m.SA.FAPi significantly increased two weeks after MI induction (MI: 2.1 ± 0.2%ID/g, n = 7 vs. SHAM: 1.1 ± 0.2%ID/g, n = 5; p = 0.002), confirmed by ex vivo autoradiography. No significant difference was observed at six weeks post-MI (MI: 1.1 ± 0.1%ID/g, n = 4 vs. SHAM: 0.8 ± 0.0%ID/g, n = 3), indicating infarct healing completion. In contrast, TAC mice showed increased uptake after six weeks (TAC: 1.8 ± 0.2%ID/g, n = 6; p = 0.007), related to interstitial fibrosis progression. Consistently, high-stretched cardiac fibroblasts demonstrated a higher uptake compared to low-stretched conditioned ones, suggesting the stretch mediates regulation of FAP. Conclusions: This study demonstrated the efficacy of [68Ga]Ga-DATA5m.SA.FAPi for longitudinal imaging of cardiac fibrosis in response to different cardiac injuries. In vivo FAP imaging during cardiac remodeling may serve as a valuable tool for diagnosing and predicting disease progression, ultimately aiding in the clinical management of patients.